THE INFLUENCE OF REGIONAL GENERATED REVENUES, BLOCK GRANT, SPECIAL GRANT, FUND SHARING, PROVINCIAL GOVERNMENT TRANSFER, AND EXTRA BUDGET CALCULATION ON CAPITAL EXPENDITURE IN DISTRICTS/TOWNS OF NORTH SUMATERA WITH GROSS REGIONAL DOMESTIC PRODUCT AS MODERATING - Lestari, Yuni Br.Sitepu (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of this study was to analyze the influence of Regional Generated Revenues (PAD), Block Grant (DAU), Special Grant (DAK), Fund Sharing (DBH), Provincial Government Transfer (TPP), and Extra Budget Calculation (SiLPA) on Capital Expenditure with Gross Regional Domestic Product (PDRB) as moderating variable . The research used qualitative causal associative method with secondary data. The population was 198 data obtained from actual budget report of 33 districts/towns in North Sumatera within 6 years (2010- 2015), and the sample were taken by using cencus sampling technique. The data were analyzed by using multiple linear regression analysis and residual test.. The result of the research showed that, simultaneously, PAD, DAU, DAK, DBH, TPP and SiLPA had the influence of Capital Expenditure. Partially, PAD, DAU, DAK,  TPP and SiLPA had significant influence of Capital Expenditure in Districts/Towns in North Sumatera. Gross Regional Domestic Product could not moderate the correlation of Regional Generated Revenues, Block Grant, Special Grant, Fund Sharing, Provincial Government Transfer, and Extra Budget Calculation with Capital Expenditure